1997
DOI: 10.1176/ajp.154.5.697
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for allelic association between personality traits and the dopamine D4 receptor gene polymorphisms

Abstract: The previously reported association between dopamine D4 receptor alleles and novelty seeking was not replicated. Possible reasons for this include differences in personality inventories, ethnicity, and type I or type II errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…However, our present study of total, male or female subjects identified no significant association between any of the 3 tested SNPs in the NTR1 gene, which is closely connected to the dopamine system, and NS scores, suggesting that NTR1 is not a defining factor in the NS temperament dimension, at least in the Chinese Han genetic background. In fact, the current results are consistent with those of many previous studies that found no associations between DRD2 [44], DRD4 [44,45,46,47,48], and dopamine transporter 1 [47] gene variants and NS in different healthy populations, and that did not replicate the results that variants in the genes encoding proteins in the dopamine system were related to NS trait scores.…”
Section: Discussionsupporting
confidence: 85%
“…However, our present study of total, male or female subjects identified no significant association between any of the 3 tested SNPs in the NTR1 gene, which is closely connected to the dopamine system, and NS scores, suggesting that NTR1 is not a defining factor in the NS temperament dimension, at least in the Chinese Han genetic background. In fact, the current results are consistent with those of many previous studies that found no associations between DRD2 [44], DRD4 [44,45,46,47,48], and dopamine transporter 1 [47] gene variants and NS in different healthy populations, and that did not replicate the results that variants in the genes encoding proteins in the dopamine system were related to NS trait scores.…”
Section: Discussionsupporting
confidence: 85%
“…Simultaneously, Benjamine et al5 reported an association between the same DRD4 polymorphism and the excitement-seeking item measured by the NEO PI-R (Revised NEO Personality Inventory) questionnaire. Some further studies have found a relation between the long DRD4 VNTR allele and a higher NS score,6,7 while others have not found such an association 8,9…”
Section: Introductionmentioning
confidence: 95%